(untitled) (Bangladesh Journal of Pharmacology, 2016)
The aim of the present study was to synthesize epoxide derivative of alloimperatorin and evaluating its antitumor and apoptotic effects in acute myeloid leukemia HL-60 cells. The cytotoxic effects were demonstrated by MTT assay. Fluorescence microscopy along with flow cytometry were performed to evaluate the effect of alloimperatorin epoxide on apoptosis and cell cycle. In vitro wound healing assay was performed to study compounds effect on cancer cell migration. The results indicated that alloimperatorin epoxide (IC50 = 32.1 µM) was much more effective in inhibiting HL-60 cancer cell growth as compared to alloimperatorin (IC50 = 128 µM). Further, alloimperatorin epoxide induced apoptosis related morphological alterations in HL-60 cells including blebbing of plasma membrane, DNA fragmentation and formation of apoptotic bodies. Alloimperatorin epoxide also led to G2/M phase cell cycle arrest and suppressed HL-60 cancer cell migration indicating that this compound may be a promising candidate for the treatment of cancer metastasis.